University Students’ Perception toward Plagiarism - Darmayanti, K.S.D.; Santosa, M.H.; Kusuma, I.P.I. (Universitas Pendidikan Ganesha, 2018)
This study aimed to investigate students’ perception toward plagiarism, students’ reasons to commit plagiarism and students’ ways to avoid plagiarism in University in North Bali. This study employed explanatory sequential mixed method with 175 students from different departments and faculties. This data were collected questionnaire and interview. The questionnaire consisted of 30 items statements about plagiarism, students’ experiences about plagiarism, students’ reasons to commit plagiarism and students’ ways to avoid plagiarism. This data were analyzed quantitatively. The result of this study showed score of students’ perception toward plagiarism was 3.9981 in interval 3.696654.64995. Based on qualification level, the score of students’ perception toward plagiarism categorized high and the qualification was positive. It means the students’ understand about plagiarism. It can be concluded students understand about plagiarism and the result students are expected to avoid plagiarism no matter. For further research it suggested to conduct similar study with larger participants.